Coral diseases and compromised health prevalence in Gili-Noko Waters, Bawean Island, Indonesia - MUHAMMAD ARIF ASADI; ADITYA NATA AZHARI; AULIA LANUDIA FATHAH; ANDIK ISDIANTO; ARIEF SETYANTO; LUTHFIL HAKIM SALIM; RIQKI YOGA APRILIANTO; MAHENDRA AHMAD MUNIF; MOHAMAD FAISAL (Society for Indonesian Biodiversity, 2025)
Abstract. Asadi MA, Azhari AN, Fathah AL, Isdianto A, Setyanto A, Salim LH, Aprilianto RY, Munif MA, Faisal M. 2025. Coral diseases and compromised health prevalence in Gili-Noko Waters, Bawean Island, Indonesia. Biodiversitas 26: 1433-1442. Coral reefs have important ecological and economic functions. Bawean Island, Indonesia known for its natural beauty and rich marine resources, has become an important tourism destination. This research aims to understand how environmental parameters and human activities influence the prevalence of coral diseases and their impact on coral reef diversity. The measurement of coral cover used a combination of Line Intercept Transect (LIT) and transect quadrants, while field data collection for coral disease assessment used a belt transect with a size of 20x2 m. The findings showed that coral cover in Gili-Noko Waters ranged from 65.90% to 74.86%, with various types of coral diseases identified. Identified diseases include Pigmentation Response (PR), Growth Anomaly (GA), White Band Disease (WBD), Yellow Band Disease (YBD), White Patch (WP), White Syndromes (WS), Unusual Bleaching Patterns (BL), Ulcerative White Spot (UWS), Sediment Damage (SD), and Fish Bites (FB). These diseases affect the coral genera. Acropora (437 colonies), Isopora (345 colonies), Echinopora (8 colonies), Porites (160 colonies), Platygyra (12 colonies), Favia (98 colonies), Astreopora (22 colonies), and Lobophyllia (3 colonies). Stylophora (2 colonies), Millepora (13 colonies), and Fungia (7 colonies). The correlation between environmental parameters and disease prevalence shows that dissolved oxygen levels have the most significant influence. Human activities have a significant impact on the health of coral reefs, highlighting the need for effective management and ongoing conservation efforts.